Integrated nematode management State-of-the-art and visions for the future - Sikora, Richard; Desaeger, Johan; Molendijk, Leendert (CABI, 2021)
This book outlines the economic importance of specific plant parasitic nematode problems on the major food and industrial crops and presents the state-of-the-art management strategies that have been developed to reduce specific nematode impacts and outlines their limitations. Case studies to illustrate nematode impact in the field are presented and future changes in nematode disease pressure that might develop as a result of climate change and new cropping systems are discussed.